2020
DOI: 10.1177/0040517519896757
|View full text |Cite
|
Sign up to set email alerts
|

New approach for the prediction of compression pressure using the cut strip method

Abstract: The main objective of the current research is the development of a new mathematical model for the prediction of compression pressure based on the incorporation of some new parameters. These new parameters include deformed width (wf), true stress ([Formula: see text]), true/logarithm strain ([Formula: see text]), true modulus of elasticity ([Formula: see text]), along with measurement of engineering stress ([Formula: see text]), engineering strain ([Formula: see text]) and engineering modulus of elasticity ([Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Very recently, a new practical engineering approach to modelling, measuring and predicting the compression from a compression garment used a cut-strip method to develop two new mathematical models based on 'true Young's modulus' and 'engineering Young's modulus'. Through comparison with Hooke's law and Laplace's law and previous models of Leung et al [458] and Dubuis et al [459], using linear regression to assess the experimentally-measured compression pressure results, it was found that the newly-developed models were more precise and accurate than the previous models [460].…”
Section: Engineering the Pressure Garmentmentioning
confidence: 93%
“…Very recently, a new practical engineering approach to modelling, measuring and predicting the compression from a compression garment used a cut-strip method to develop two new mathematical models based on 'true Young's modulus' and 'engineering Young's modulus'. Through comparison with Hooke's law and Laplace's law and previous models of Leung et al [458] and Dubuis et al [459], using linear regression to assess the experimentally-measured compression pressure results, it was found that the newly-developed models were more precise and accurate than the previous models [460].…”
Section: Engineering the Pressure Garmentmentioning
confidence: 93%
“…Different elongations and compressions are achieved at certain cylinder diameters. In order to imitate the stocking position on the leg, it is mounted on an artificial leg, which is most commonly wooden, and the compression is measured in different places [ 16 , 25 , 26 ]. When measuring the stocking compression on a person, i.e., on a real leg, measurements are performed in a similar way.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained on a model and the human leg will be different [ 10 , 11 , 16 ]. The results of measuring stocking compression at different bidirectional elongations or those obtained through different measuring methods will also differ [ 26 , 27 , 28 ]. In any case, the relevant compression values are those measured on the human leg, and any other results should be compared or adjusted to those.…”
Section: Introductionmentioning
confidence: 99%